Learning Strategy for Market Main Discussion Based Outdoor Learning in Increasing Conceptual Understanding of Social Studies - Casriatun, Casriatun; Hardati, Puji; Banowati, Eva (Universitas Negeri Semarang, 2019)
Lower students interest in social studies is influenced by learning strategies that have not been able to meet the demands of development and needs. The purpose of this study is to analyze social studies learning in market main discussion and market agree based on outdoor learning in improving conceptual understanding of social science knowledge. The research method used is qualitative research design with phenomenology. Informants in this study were teachers, students, traders in the market. Data collection techniques by observation, interviews, and documentation. The validity of the data in this study uses triangulation techniques. The results showed that the students of Public Junior High School 1 Bodeh, Pemalang Regency, in the process of outdoor learning in the market could increase conceptual knowledge with an achievement level classically 87.5%. This learning strategy can be used for innovation in the learning process that is appropriate to the development and needs of students.